The Effect of Financial Performance on Company Value in Manufacturing Companies Listed on the Indonesia Stock Exchange - Agung Putrawan; Munawarah; Muslimin; Erwan Sastrawan Farid (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2026)
This study aims to analyze the influence of financial performance on the value of companies in manufacturing companies listed on the Indonesia Stock Exchange. Financial performance is an important indicator for investors and management in assessing a company's ability to generate profits, maintain liquidity, and manage its funding structure efficiently. A company's value reflects the market's perception of its outlook and sustainability, making it an important factor in investment decision-making. This study uses a quantitative, explanatory approach. The data used is secondary data obtained from the annual financial statements of manufacturing companies published on the Indonesia Stock Exchange and from the companies' official sources. The research sample was selected using a purposive sampling technique based on specific criteria. Data analysis was carried out using panel data regression to test the influence of financial performance variables on the company's value. Financial performance variables are proxied by profitability, liquidity, and leverage ratios, while company value is proxied by Price-to-Book Value (PBV). The results of the research are expected to make theoretical contributions to the development of financial management studies, as well as practical contributions for investors, company management, and other stakeholders in understanding the factors that affect company value in the Indonesian capital market.